The Consistency of Indonesia's Defense Attitude Towards Palestine: History and Causes - Aswar, Hasbi; Widyrianto, Faramita Rahmadany (Unisia, 2025)
Indonesia's support for Palestine is a consistent attitude rooted in the principles of anti-colonialism, historical solidarity, and a free and active foreign policy, as stated in the Preamble to the 1945 Constitution. Since the recognition of the Palestine Liberation Organization (PLO) in 1974 and the official recognition of Palestine as an independent state in 1988, Indonesia has shown its commitment to supporting Palestinian independence. This study aims to analyse Indonesia's historical role in defending Palestine and the diplomatic steps taken in response to the latest developments in the conflict. This study used a qualitative approach with descriptive and historical analysis methods. Data were obtained through literature studies from various secondary sources, including academic journals, official reports, and statements by the Indonesian government in various international forums. The results of this study show that Indonesia consistently supports Palestine through diplomacy at the United Nations and the Organization of Islamic Cooperation (OIC), as well as through humanitarian assistance. In the face of Israeli aggression in 2023-2024, Indonesia is taking strategic steps in the form of diplomatic condemnation, raising global support, and increasing humanitarian assistance for the Palestinian people. Indonesia plays an important role in supporting Palestine through historical and sustainable diplomacy. Indonesia's foreign policy adheres to the principles of anti-colonialism and the struggle for human rights, making it one of the most vocal countries in supporting Palestine in the international arena.